Nighttime particle growth observed during spring in New Delhi: Evidences for the aqueous phase oxidation of SO2. (September 2018) - Sarangi, Bighnaraj; Aggarwal, Shankar G.; Kunwar, Bhagawati; Kumar, Sudhanshu; Kaur, Ravleen; Sinha, Deepak; Tiwari, Suresh; Kawamura, Kimitaka
Abstract: Aerosol size distributions were measured using a scanning mobility particle sizer (SMPS), and also PM1 (particulate matter ≤ 1 μm in aerodynamic diameter) samples were collected in parallel at a representative site in New Delhi during spring in 2013 and 2014. Based on the temporal variation of particle count mean diameter (CMD), sampling periods are characterized as growth events and non-growth events. Particle size distribution measurements suggest that some consecutive nights experienced unique nighttime subsequent growth of particles, which sustained for a longer period. Average particle growth rate measured during growth events was 5.64 ± 3.03 nm h −1 . Atmospheric trace gas concentrations and meteorological data show that these growth events (nighttime) are influenced by higher concentrations of gases, e.g., NO2 (56.5 ± 29.7 μg m −3 ), SO2 (9.34 ± 1.14 μg m −3 ) and RH (45.7 ± 9.5%) than those of non-growth events (daytime) (37.9 ± 18.6 μg m −3, 7.19 ± 2.08 μg m −3 and 37.7 ± 6.9%, respectively). Further, analysis of PM1 samples collected during the study period shows that the particulate water-soluble organic carbon (WSOC) (12.7 ± 4.1 μg m −3 ), NH4 + (9.4 ± 3.2 μg m −3 ), SO4 2− (2.03 ± 0.70 μg m −3 ), K + (1.06 ± 0.40 μg m −3 ), and NO2 −  + NO3 − (0.59 ± 0.36 μg m −3 ) are the major contributors of particulate mass, wherein NH4 +, SO4 2−, K +, NO2 −  + NO3 − mass concentrations were higher during growth events. Correlation study shows that nighttime aerosol composition during growth (in sub-micron range) events are more enriched by inorganic species (i.e., NH4 NO3, (NH4 )2 SO4 and H2 SO4 vapors) as compared to organics (i.e., WSOC, does not show much difference in growth events and non events). Our results suggest that nighttime sulfate formation at the site is mostly mediated by high NO2 and NH3 at elevated RH. For the formation of sulfate and other inorganic species, a nighttime atmospheric chemistry is proposed, which is linked to particle growth. Growth events observed typically in nighttime have both biomass burning and anthropogenic influences as indicated by high concentrations of WSOC, K + and black carbon in PM1 and carbon monoxide in gas phase. Highlights: Nighttime aerosol sulfate formation is mostly mediated by high NO2 and NH3 at elevated RH. For this formation, a nighttime atmospheric chemistry is proposed, which is linked to particle growth. Growth events observed typically in nighttime have both biomass burning and anthropogenic influences.